2022
DOI: 10.1155/2022/1941077
|View full text |Cite|
|
Sign up to set email alerts
|

DDTC Suppresses Ovarian Cancer Development via the PI3K/AKT/mTOR Signaling Pathway

Abstract: In prior research, 6,12-diphenyl-3,9-diazatetraasterane-1, 5, 7, 11-tetracarboxylate (DDTC) has been shown to be an effective inhibitor of the growth of the SKOV3 and A2780 ovarian cancer (OC) cell lines. Flow cytometry analyses indicated that DDTC was able to suppress P-CNA expression at the protein level within OC cells, while RNA-seq indicated that DDTC treatment was associated with marked changes in gene expression profiles within A2780 cells. Molecular docking analyses suggested that DDTC has the potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
2
4
0
Order By: Relevance
“…Negative prognostic genes such as OLFML2B may promote the adhesion of OV cells to certain components in the ECM through their surface receptors and activate the expression of metalloproteinases to degrade the matrix, thereby promoting cancer progression. Meng Li et al showed that DDTC can effectively inhibit cell growth through the PI3K/AKT/mTOR signaling pathway, thereby inhibiting the development of OV [31], and our study also showed that the functions of CCND1, COL1A1, COL1A2, LPAR3, etc. are mainly enriched In PI3K-A, TGF-β, Hippo and other signaling pathways.…”
Section: Discussionsupporting
confidence: 71%
“…Negative prognostic genes such as OLFML2B may promote the adhesion of OV cells to certain components in the ECM through their surface receptors and activate the expression of metalloproteinases to degrade the matrix, thereby promoting cancer progression. Meng Li et al showed that DDTC can effectively inhibit cell growth through the PI3K/AKT/mTOR signaling pathway, thereby inhibiting the development of OV [31], and our study also showed that the functions of CCND1, COL1A1, COL1A2, LPAR3, etc. are mainly enriched In PI3K-A, TGF-β, Hippo and other signaling pathways.…”
Section: Discussionsupporting
confidence: 71%
“…In this study, these differential genes associated with OV progression were also enriched in multiple pathways such as ECM receptor interaction, focal adhesion, collagen metabolic process, and cell response to amino acid stimulation. Negative prognostic genes such as OLFML2B may promote the adhesion of OV cells to certain components in the ECM through their surface receptors and activate the expression of metalloproteinases to degrade the matrix, thereby [38]. Similarly, our study also showed that the functions of genes like CCND1, COL1A1, COL1A2, LPAR3, etc.…”
Section: Discussionsupporting
confidence: 62%
“…Negative prognostic genes such as OLFML2B may promote the adhesion of OV cells to certain components in the ECM through their surface receptors and activate the expression of metalloproteinases to degrade the matrix, thereby promoting cancer progression. Meng Li et al showed that DDTC could effectively inhibit cell growth through the PI3K/AKT/mTOR signaling pathway, thereby inhibiting the development of OV [ 38 ]. Similarly, our study also showed that the functions of genes like CCND1, COL1A1, COL1A2, LPAR3, etc.…”
Section: Discussionmentioning
confidence: 99%
“…16 Several clinical studies have shown that the PI3K pathway is a promising target for the treatment of OC. [17][18][19] T-Complex 1 (TCP1) is significantly upregulated in OC and promotes OC cell expansion through regulation of PI3K/AKT/mTOR signaling. 20 Knockdown of METTL3 has been shown to inhibit development of OC through inhibition of the PI3K/Akt/mTOR pathway.…”
Section: Introductionmentioning
confidence: 99%